PENGARUH PENDAMPINGAN PENGAWAS, SUPERVISI KEPALA SEKOLAH DAN BUDAYA SEKOLAH TERHADAP KOMITMEN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA PADA SEKOLAH DASAR NEGERI DI KABUPATEN ACEH TAMIANG - Muhammad Bahtiar; Marwan Marwan; Saiful Bahri (Universitas Islam Negeri Sumatera Utara Medan, 2025)
The objectives of this research are as follows: (1) To identify and analyze the influence of school supervisor mentoring on teachers' commitment to implementing the Merdeka Curriculum in public elementary schools in Aceh Tamiang Regency. (2) To identify and analyze the influence of principal supervision on teachers' commitment to implementing the Merdeka Curriculum in public elementary schools in Aceh Tamiang Regency.(3) To identify and analyze the influence of school culture on teachers' commitment to implementing the Merdeka Curriculum in public elementary schools in Aceh Tamiang Regency. (4) To identify and analyze the combined influence of school supervisor mentoring, principal supervision, and school culture on teachers' commitment to implementing the Merdeka Curriculum in public elementary schools in Aceh Tamiang Regency. This research uses a quantitative method with an ex post facto approach. The population consists of 278 individuals, with a sample of 164 individuals selected via purposive sampling using Slovin's formula at a 5% error level. Data collection employs a Likert scale questionnaire, and data processing uses path analysis. Partial research findings show direct influences as follows: (1) School supervisor mentoring on teachers' commitment: 0.122, (2) Principal supervision on teachers' commitment: 0.212, (3) School culture on teachers' commitment: 0.627 (4) Simultaneous influence of supervisor mentoring, principal supervision, and school culture on teachers' commitment: 0.726